Learning by Outward FDI: Evidence from Chinese Manufacturing Enterprises - Yaping, Yang; Zhuhong, Wu; Yutian, Chen (Panoeconomicus, 2017)
Using firm-level data of Chinese manufacturing enterprises between 1998 and 2007, we investigate the existence and channels of "learning by outward FDI". Difference-in-differences estimation reveals that productivity of Chinese parent firms is significantly improved by their outward foreign direct investment and the learning effects form a “V” shape in the following years. There is no significant difference in learning effects between state-owned enterprises and non-state-owned enterprises; neither do we find any evidence that investing in countries with advanced technology gives more learning effects. In addition, we find that learning effects mainly come from technology transfer, technology spillovers and an enlarged production scale.Key words: Outward foreign direct investment, Learning effects, Learning channels, Difference-in-difference estimator.JEL: D24, F21, F23.Korišćenjem podataka o Kineskim proizvodnim preduzećima na nivou preduzeća između 1998. i 2007. godine, istražujemo postojanje i kanale “učenja na osnovu nepovratnih stranih direktnih investicija”. Procena razlika-u-razlici otkriva da je produktivnost Kineskih matičnih preduzeća značajno poboljšana njihovim nepovratnim stranim direktnim ulaganjima, a efekti učenja formiraju “V” oblik u narednim godinama. Ne postoji značajna razlika u efektima učenja između preduzeća u državnom vlasništvu i preduzeća koja nisu u državnom vlasništvu; niti nalazimo bilo kakve dokaze da investiranje u zemlje sa naprednom tehnologijom daje značajniji efekat učenja. Pored toga, tvrdimo da efekti učenja uglavnom potiču od prenosa tehnologije, eksternih efekata prenosa tehnologije i uvećanog obima proizvodnje.Ključne reči: nepovratne strane direktne investicije, efekti učenja, kanali za učenje, procena razlika-u razlici.